Are asymmetries in imperative negation based in usage? - Daniel Van Olmen (Linguistic Typology at the Crossroads)
This article extends the study of (a)symmetries in negation to the domain of (negative) imperatives. It examines a balanced sample of the world’s languages for distinctions in tense, direction/location and intersubjectivity and observes that, like with asymmetry in standard negation, they are often neutralized from positive to negative but not vice versa. Intersubjective marking is found to be somewhat exceptional in that the opposite situation does occasionally occur. The article also tests whether and confirms that these asymmetries are grounded in usage patterns, with a corpus investigation of English and Dutch (negative) imperatives. It proposes negation’s discourse presuppositionality, which has been argued to account for neutralization in standard negation, as an explanation for most but not all of these typological and usage-based results in imperative negation too. It nevertheless makes a case for other, more imperative-specific motivations as well.